The relationship of takaful agents’ Islamic ethical behaviour towards customers’ satisfaction, trust and commitment: a preliminary analysis - Che Mohd Salleh, Marhanum; Abdullah, Nurdianawati Irwani; Razali, Siti Salwani (World Business Institute, 2013)

(untitled)
Takaful agents have become among the important distribution channels in Takaful industry. Besides selling Takaful products, the agents must practice Islamic ethical behaviour in dealing with customers. This research seeks to investigate the relationship between Takaful agents’ Islamic ethical behaviour and customers’ satisfaction, trust and commitment. As there are limited studies conducted in this area, this research provides a preliminary analysis with 30 Takaful customers. Data were collected through survey research design using questionnaire as the research instrument. Results indicate that there are positive significant relationship between Takaful agents’ Islamic ethical behaviour towards customers’ satisfaction, trust and commitment. However, majority of the respondents were not fully agreed about the practice of Islamic ethical behaviour by their Takaful agents understudy. Thus, Takaful operators need to play their role in guiding and encouraging their agents to practice the Islamic ethical behaviour in marketing Takaful products in order to ensure the publics’ satisfaction, trust, and commitment towards their Takaful scheme.